Coexistence of Primary Sjögren’s Syndrome and Autoimmune Gastritis With Pernicious Anemia and Subacute Combined Degeneration of the Spinal Cord: Case Report and Literature Review - Zhan, Hao-Su; Yao, Xin; Hu, Hai-Yi; Han, Yan-Fei; Yue, Bing; Sun, Li-Ying; Wang, Yong-Jun (Frontiers in Immunology, 2022)
Background Autoimmune gastritis (AIG) and Primary Sjögren’s syndrome (pSS) are both autoimmune diseases with low prevalence in China. Subacute combined degeneration (SCD) of the spinal cord is the most common neurological manifestation of vitamin B12 deficiency. Until now, a patient with pSS and complications of AIG including SCD has not been reported. Case presentation A 69-year-old woman presented with palpitations and symmetrical and progressive numbness in her hands and feet. The patient had a sense of stepping on cotton and could not write or walk without help. We reviewed the patient’s history and analyzed her blood tests, imaging, gastroscopic findings, and pathological results. The patient fulfilled the criteria of AIG, pSS, spinal cord SCD and early pernicious anemia (PA) simultaneously. Although pSS can lead to reduction of vitamin B12, this is the first overlapping case of pSS with spinal cord SCD. After symptomatic treatment, the patient returned to a normal life. Conclusions This first report about the coexistence of pSS and complications of AIG including SCD and PA will promote a better understanding of the relationship between these diseases.